Evaluation of the Biolabo Turbidimetric Assay for Automated Determination of Haemoglobin A1c - Lorenza Fagnani; Simonetta De Angelis; Pierangelo Bellio; Patrizia Frascaria; Rita Tennina; Giovanni Alloggia; Francesco Gentile; Alessandra Piccirilli; Mariagrazia Perilli; Giuseppe Celenza (Diagnostics)
Background/Objectives: The determination of glycated haemoglobin (HbA1c) is a cornerstone of the diagnosis and management of diabetes mellitus, serving as a reliable biomarker for assessing long-term glycaemic control. While high-performance liquid chromatography (HPLC) is regarded as the gold standard for HbA1c measurement, its widespread adoption is limited by high costs, operational complexity, and resource requirements. Alternative methodologies, including immunoturbidimetric assays, have garnered interest as practical solutions. This study evaluates the analytical performance of an immunoturbidimetric method for HbA1c determination and its comparability with a validated HPLC method. Methods: The evaluation process was conducted in accordance with the Clinical and Laboratory Standards Institute (CLSI) guidelines. The results from 178 human sample leftovers, covering the medical decision range, were compared with those obtained using the HPLC-based Menarini ADAMS A1c HA-8180T system. The analytical performance regarding repeatability and within-laboratory imprecision was also assessed. The probability risk of misinterpreting the analytical results was also calculated. Results: The Passing–Bablok regression indicated a strong correlation between the two methods, with a slope of 1.00 (95% CI: 1.00 to 1.04). The Bland–Altman analysis confirmed minimal systematic differences, showing a mean bias of −0.07% for NGSP and −0.74 mmol/mol for IFCC, both falling within the predefined total allowable error (ATE) limits. Imprecision studies demonstrated excellent repeatability and intermediate precision, with coefficients of variation (CV) ranging from 0.68% to 2.4% across all levels. The risk assessment of diagnostic misinterpretation indicated minimal deviation from an ideal analytical system, in which the measurement uncertainty was regarded as zero. Conclusions: The findings establish the immunoturbidimetric method as a reliable and cost-effective alternative to HPLC for routine HbA1c determination. Its strong analytical performance, combined with operational efficiency, makes it a valuable tool for laboratories, particularly in resource-limited settings, enhancing access to high-quality diabetes monitoring.